Microglia: The Hub of Intercellular Communication in Ischemic Stroke - Zhang, Yunsha; Lian, Lu; Fu, Rong; Liu, Jueling; Shan, Xiaoqian; Jin, Yang; Xu, Shixin (Frontiers in Cellular Neuroscience, 2022)
Communication between microglia and other cells has recently been at the forefront of research in central nervous system (CNS) disease. In this review, we provide an overview of the neuroinflammation mediated by microglia, highlight recent studies of crosstalk between microglia and CNS resident and infiltrating cells in the context of ischemic stroke (IS), and discuss how these interactions affect the course of IS. The in-depth exploration of microglia-intercellular communication will be beneficial for therapeutic tools development and clinical translation for stroke control.